The effect of actuator and sensor placement on the active control of rotor unbalance - Johnson, Marty E.; Nascimento, Luiz P. [UNESP]; Kasarda, Mary; Fuller, Chris R. (My University, 2003)
This paper investigates both theoretically and experimentally the effect of the location and number of sensors and magnetic bearing actuators on both global and local vibration reduction along a rotor using a feedforward control scheme. Theoretical approaches developed for the active control of beams have been shown to be useful as simplified models for the rotor scenario. This paper also introduces the time-domain LMS feedforward control strategy, used widely in the active control of sound and vibration, as an alternative control methodology to the frequency-domain feedforward approaches commonly presented in the literature. Results are presented showing that for any case where the same number of actuators and error sensors are used there can be frequencies at which large increases in vibration away from the error sensors can occur. It is also shown that using a larger number of error sensors than actuators results in better global reduction of vibration but decreased local reduction. Overall, the study demonstrated that an analysis of actuator and sensor locations when feedforward control schemes are used is necessary to ensure that harmful increased vibrations do not occur at frequencies away from rotor-bearing natural frequencies or at points along the rotor not monitored by error sensors.
Keywords: Actuators; Control systems; Error analysis; Frequency domain analysis; Magnetic bearings; Natural frequencies; Sensors; Time domain analysis; Vibrations (mechanical); Active magnetic bearings (AMB); Rotors